Screen for IDH1, IDH2, IDH3, D2HGDH and L2HGDH mutations in glioblastoma. - Daniel Krell; Mawuelikem Assoku; Malcolm Galloway; Paul Mulholland; Ian Tomlinson; Chiara Bardella (PLoS ONE)
Isocitrate dehydrogenases (IDHs) catalyse oxidative decarboxylation of isocitrate to α-ketoglutarate (α-KG). IDH1 functions in the cytosol and peroxisomes, whereas IDH2 and IDH3 are both localized in the mitochondria. Heterozygous somatic mutations in IDH1 occur at codon 132 in 70% of grade II-III gliomas and secondary glioblastomas (GBMs), and in 5% of primary GBMs. Mutations in IDH2 at codon 172 are present in grade II-III gliomas at a low frequency. IDH1 and IDH2 mutations cause both loss of normal enzyme function and gain-of-function, causing reduction of α-KG to D-2-hydroxyglutarate (D-2HG) which accumulates. Excess hydroxyglutarate (2HG) can also be caused by germline mutations in D- and L-2-hydroxyglutarate dehydrogenases (D2HGDH and L2HGDH). If loss of IDH function is critical for tumourigenesis, we might expect some tumours to acquire somatic IDH3 mutations. Alternatively, if 2HG accumulation is critical, some tumours might acquire somatic D2HGDH or L2HGDH mutations. We therefore screened 47 glioblastoma samples looking for changes in these genes. Although IDH1 R132H was identified in 12% of samples, no mutations were identified in any of the other genes. This suggests that mutations in IDH3, D2HGDH and L2HGDH do not occur at an appreciable frequency in GBM. One explanation is simply that mono-allelic IDH1 and IDH2 mutations occur more frequently by chance than the bi-allelic mutations expected at IDH3, D2HGDH and L2HGDH. Alternatively, both loss of IDH function and 2HG accumulation might be required for tumourigenesis, and only IDH1 and IDH2 mutations have these dual effects.